Associations of osteoprotegerin with coronary artery calcification among women with systemic lupus erythematosus and healthy controls. (May 2018) - Poornima, I G; Shields, K; Kuller, L H; Manzi, S M; Ramsey-Goldman, R; Richardson, C; Rhew, E; Dunlop, D D; Song, J; Edmundowicz, D; Kondos, G T; Carr, J J; et al.
Objective: We tested the hypothesis that higher circulating levels of osteoprotegerin (OPG) are related to higher levels of coronary artery calcification (CAC) among women with systemic lupus erythematosus (SLE) compared with healthy controls (HCs). Methods: Among 611 women in two age- and race-matched SLE case-control studies, OPG was assayed in stored blood samples (HEARTS: plasma, n cases/controls = 122/124, and SOLVABLE: serum, n cases/controls = 185/180) and CAC was measured by electron beam computed tomography. Results: In both studies, SLE patients had higher OPG and CAC levels than HCs. Higher OPG was associated with high CAC (>100 vs.100) among SLE, and with any CAC (>0 vs. 0) among HCs. Multivariable-adjusted OR (95% CI) for OPG tertile 3 vs. 1 was 3.58 (1.19, 10.76), p trend = 0.01 for SLE, and 2.28 (1.06, 4.89), p trend = 0.04 for HCs. Associations were attenuated when age-adjusted, but remained significant for HC women aged ≥ 40 and SLE women aged ≥ 50. ROC analyses identified 4.60 pmol/l as the optimal OPG cutpoint for predicting high CAC (>100) among SLE patients with sensitivity = 0.74 and specificity = 0.61, overall, but 0.92 and 0.52, respectively, for SLE patients aged ≥ 50. Conclusion: Our cross-sectional results suggest that higher OPG levels are related to higher CAC levels among women with SLE vs. healthy controls.